An empirical analysis of debit card interchange fee regulation: Evidence from Brazil - Daniel Tavares de Castro; Emerson Schmitz; Monique de Abreu Azevedo (Latin American Journal of Central Banking (LAJCB), 2023)
This paper presents an empirical analysis of the introduction, in October 2018, of maximum thresholds ("caps") on debit card interchange fees for domestic payment cards in Brazil. We investigate the behavior of card issuers' revenues from debit and credit card interchange fees, the merchant discount rate (MDR) of debit transactions, debit and credit card usage, and debit card scheme fees paid by card issuers and acquirers after the cap. We find a gradual and increasing reduction in the MDR, from 6.0% in 2018Q4 to 22.8% in 2020Q1. Additionally, we observe a statistically significant difference between debit and credit card MDR in 2019Q4 and 2020Q1. The cap reduces card issuers' earnings from the debit card interchange fee proportionally to the cut but does not affect similar revenues from credit cards. Overall, there is no evidence that the regulation of the debit card interchange fee changes the dynamics of debit card usage or that it changes debit card scheme fees.
Keywords: 330; debit card; interchange fee; merchant discount rate; regulatory intervention